Theranostics: Radiolabelled Polymeric Materials for Imaging and Treatment of Cancer: Quo Vadis? (Adv. Healthcare Mater. 6/2017). Issue 6 (March 2017) - Pant, Kritee; Sedláček, Ondřej; Nadar, Robin A.; Hrubý, Martin; Stephan, Holger
Abstract : The utilization of polymeric nanomaterials in combination with imaging‐ and/or therapy‐related radionuclides holds a promising potential for cancer diagnosis and treatment. In article number 1601115, Holger Stephan, Martin Hrubý, and co‐workers review the recent advances and emerging opportunities of tumour‐targeted radiolabelled polymeric nanomaterials for both non‐invasive imaging and treatment of cancer.